The modern telephone exchange - Hess, Harry P.; Wolf, George (My University, 1905)
Introduction (thesis A): The history of the telephone, from the most crude methods of speech transmission to its present Perfection, is a most interesting one. The knowledge of the principles of electromagnetism dates back to the year 1820, and with this date begins the history of our modern telephone. The telephone of today has not been work of one particular inventive genius, but has been developed step by step by many scientists and inventors whose names stand conspicuous in connection with electrical progress. In 1820, Oersted discovered that a magnetic needle tends to place itself at right angles to a wire carrying a current. To ampere we are indebted for the laws upon which present electromagnetic theory is based. Arago and Davy discovered that if a current be caused to flow through an insulated wire wrapped around a core of steel the latter would exhibit magnetic properties. In 1825 Sturgeon made an electro-magnet as we know it today. Farady and Henry discovered the converse of these laws of electro-magnetism that If the intensity of a magnetic field enclosed by a conductor, be changed, a current of electricity will flow in the conductor. The current will flow only while such change is taking place and its strength depends directly upon the rate of change. These laws form the root of all telephone practice and by their various applications the telephone has been brought to its present perfection.

Introduction (thesis B): To thoroughly appreciate the convenience of the modern telephone practice, it is essential to take a brief review of the apparatus which has formerly been used in the telephone exchange office. While there is, without a doubt, plenty of room for improvement in almost any part of the telephone system, yet it is reasonable to expect more change in the central office apparatus that, in the receiver, transmitter, bells, magneto, etc., of the subscribers stations, since with but slight modifications, these instruments have remained the same as those used in the first successful and practical systems. However, on the other hand, one would hardly recognize the modern telephone switchboard, as being such, as compared with those of the earlier days in telephone engineering. Since the telephone is no more than a device for the saving of time and labor, it is and will be imperfect until the time and labor of operating together with the cost, are reduced to a minimum. As the subscriber's instruments are made at present so that they are ready for use as soon as the receiver is placed to the ear, it is self-evident that all delay is in making connections at central and calling the desired party to the phone. The latter fault can be corrected only by having a telephone clerk at each subscriber's station, whose business it is to answer the "phone" exclusively. From the standpoint of the central station manager this point is of but very little interest as his responsibility ceases as soon as connections are made and the calling current sent. But the convenience and rapidity of making connections is of vital importance to him, and very little experience is required to show him that with the most modern, and convenient apparatus he is enabled to not only operate a larger system with fewer "central girls", but at the same time better service is rendered to his patrons.
Citation: Hess, Harry P. and Wolf, George. The modern telephone exchange. Senior thesis, Kansas State Agricultural College, 1905.
Morse Department of Special Collections
Keywords: Capacity and Inductance; Object and Necessity; Origin and Evolution; Lamp Signalling Systems; Apparatus; Theses